Du paysage industriel au paysage de l’eau. La trajectoire paysagère originale d’un ancien faubourg industriel, Meurthe-Canal à Nancy - Léopold Barbier (Bulletin de l’Association de Géographes Français)
From the mid-19th century, Nancy, a medium-sized town in eastern France, experienced the growth of an industrial district on flood plots between the river and the historic heart of the town, with all the characteristics of an industrial suburb. After the Second World War, this outlying industrial suburb went into decline, and from 1980/1990, major urban development projects were planned to renew an area that had become dysfunctional. Having brought a capricious river under control and radically transformed the central part of the district, the front line of urban renewal now concerns the northern part of the district in particular, with a notable change in the way the industrial heritage still present in the landscape is taken into account. How, then, can we characterise the major landscape trajectories of the district: are the inherited industrial landscapes valued, ignored, destroyed, or integrated into a new transition that favours river landscapes in the city?